Effectiveness of Intervention Program on Primary School Pupils’ about Hand-washing Practices - Riyadh Saad Atshan (Universitas Muhammadiyah Sidoarjo, 2024)
This quasi-experimental study aimed to develop an intervention program to enhance hand hygiene practices among school children in Najaf Governorate. Data were collected via a questionnaire assessing demographic characteristics and hand washing behaviors. Descriptive and inferential statistics were employed for data analysis. Results revealed suboptimal hand hygiene practices, with only 58.2% of children washing their hands after using the bathroom and 63.4% after playing. Gender and age disparities were evident, with females and older children exhibiting better hand washing habits. Family dynamics also played a significant role, with children learning hand washing predominantly from their mothers, particularly when fathers were present and employed as earners. Recommendations include integrating hygiene education into school curricula and conducting targeted educational sessions to promote effective hand washing practices. These findings underscore the importance of addressing socio-demographic factors in designing interventions to improve hand hygiene among school children, thereby mitigating the spread of infectious diseases. Highlights : Importance of Hand Hygiene: The study highlights the significance of hand washing in preventing disease transmission, emphasizing its crucial role in maintaining public health. Gender and Age Disparities: Findings reveal differences in hand washing practices based on gender and age, underlining the need for targeted interventions to address these disparities. Influence of Family and Profession: The influence of family members, particularly parents, and the profession of the father on hand washing habits underscores the importance of familial and societal support in promoting good hygiene practices. Keywords : Hand hygiene, Intervention program, Quasi-experimental study, School curriculum, Educational session